The meaning and function of the Dhandhanggula Bawa song Campursari Kanca Tani song - Amirulchaq, Muhammad Arif; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
Bawa as a one of literary song like a sindhenan, janturan, gerongan, and palaran. Firstly, bawa song used in Javanese traditional or karawitan music, but since 1970th bawa song start to used in another genre, such as campursari. This research aimed to describe and analyse the meaning and function of bawa song in campursari. Sample on this research taken from bawa song with dandanggula poetic meter, that is bawa of kanca tani song. Data collected technique using record-note and in-depth interview with some informant. Data analysis of this research using qualitative-interactive with the phase are data reduction, data display, and conclusion drawing. Result of this research find that bawa on campursari song have function as intro before song sing in. Therefore, bawa also represented the meaning and message of the campursari song. So, the lyric of bawa song have suitability with content of campursari song. Bawa song in this era also have attract power on campursari fans, because there are some dialogues between bawa singer with other singer, MC, or some audience which contain sense of joke inside.